Problems in Medicine and Health Care in Karakalpakstan During the World War II - Gulmurat, Allamuratov (Buletin Antropologi Indonesia, 2024)
The article discusses the widespread prevalence of infectious intestinal diseases and parasitic typhus among the urban and rural population of Karakalpakstan during the years of World War II. It also highlights the frequent occurrence of urban doctors recording deaths from acute respiratory diseases (such as influenza and measles), as well as tuberculosis and gastrointestinal diseases (such as dysentery and hemocolitis). Regarding the heads of the sanitary-epidemiological stations (in Nukus, Chimbay, Tortkol, Muynak, and others), it is emphasized that they worked not out of fear, but conscientiously, without regard for time and effort, as expected during the wartime period. During the war years, the attitude of urban populations toward modern medicine improved significantly. It highlights that doctors such as U. Khalmuradov, V. V. Voskoboynikov, V. P. Khaneeva, A. V. Poltoratsky, I. G. Lepeshkin, E. G. Ridaeva, S. Alimov, and others gained great respect and worked diligently among the population.